2010
DOI: 10.1021/jf903911e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genistein and Daidzein on the Proliferation and Differentiation of Human Preadipocyte Cell Line

Abstract: Isoflavones are known to have several biological activities, including a hypolipidemic effect. However, the mechanism of the lipid lowering effect of genistein remains to be elucidated. There is conflicting evidence on the effect of genistein for the deposition of adipocyte tissues. We examined the effect of the isoflavones on the growth and differentiation of human preadipocyte cells, AML-I. Growth arrest accompanied by the appearance of characteristics of apoptosis was observed by genistein or daidzein treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Some studies showed that daidzein could promote adipogenic differentiation and fat deposition (Cho et al, 2010;Hirota et al, 2010;Li et al, 2011). Some studies showed that daidzein could promote adipogenic differentiation and fat deposition (Cho et al, 2010;Hirota et al, 2010;Li et al, 2011).…”
mentioning
confidence: 99%
“…Some studies showed that daidzein could promote adipogenic differentiation and fat deposition (Cho et al, 2010;Hirota et al, 2010;Li et al, 2011). Some studies showed that daidzein could promote adipogenic differentiation and fat deposition (Cho et al, 2010;Hirota et al, 2010;Li et al, 2011).…”
mentioning
confidence: 99%
“…Daidzein and equol enhanced adipocyte differentiation, formation of lipid droplets, and lipid accumulation in murine and human preadipocytes. 7,8,34 Rehfeldt et al 9 investigate the effects of dietary daidzein during late gestation on neonatal body composition and found that daidzein supplementation did not affect subcutaneous fat content but significantly elevated the concentration of fat in the whole piglet body. Similar to our results, Crespillo et al 33 observed that supplemental daidzein tended to increase the fat content in skeletal muscle and reduced that in liver of male Wistar rats.…”
mentioning
confidence: 99%
“…In animal models, puerarin also can attenuate high glucose-and diabetes-induced VSMCs proliferation . Moreover, aglycon form of puerarin could cause lipogenesis via increasing fatty acid synthase (FAS) and peroxisome proliferator-activated receptor g (PPARg) in a preadipocyte cell line (Hirota et al, 2010). In addition, wogonin was suggested to modulate atherosclerotic change in vitro (Sieveking et al, 2005), and baicalein was shown to inhibit VSMC proliferation, and suppress intimal hyperplasia after balloon vascular injury in the rat (Peng et al, 2008).…”
mentioning
confidence: 99%